Risk factors that may signify a propensity to the use of drugs in students at a public university - da Silva, Meire Luci [UNESP]; dos Santos, Nathalia M.R. [UNESP]; Barnabé, Viviani; Valenti, Vitor E. [UNESP] (Faculdade de Filosofia e Ciências, 2013)
Introduction: We sought to evaluate the risk factors that may increase the propensity to use licit and illicit drugs among students at a public university. Methods: The project involved students (n = 268) enrolled in the first and fourth years of courses in the areas of the social and biological sciences at a public university. Data collection was conducted by means of self-administered, semistructured questionnaires, based on such standardized assessment instruments as Audit, Assist, Cage and Duse. Collected data were analyzed quantitatively by calculating the percentages and evaluating the data in terms of categories of risk, classifying them by age, gender, religion, schooling, use (before or after entering university) and contexts of use. By means of this survey the researchers were able to correlate the use of drugs to the risk factors that might increase the students' propensity to use these substances. Results: The results revealed a high proportion of current drug-using students, but showed no significant differences between the first and fourth year students as regards contexts of use. However, 67% of students regarded the university environment as encouraging the use of drugs. Students pointed to such major risk factors as friends' and fellow-students' influence, university parties, excessive curiosity and desire to experiment. Conclusion: Due to the high rate of drug use among university students, by the determination of the risk factors related to the university environment and also knowing that the process of addiction is one of growing chemical dependence, the importance of the development and implementation of public health policies at all levels, especially in terms of approaches and specific interventions addressing this population, should be noted.
Keywords: College students; Psychoactive substance abuse; Risks factors